On information complexity of certain classes of operator equations - Solodkii, S. G. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
For some classes of operator equations of the second kind, we obtain an estimate of information complexity exact in order. We construct a new projection-type method that realizes the optimal estimate.